1979
DOI: 10.1093/nar/7.2.335
|View full text |Cite
|
Sign up to set email alerts
|

Localization on the viral genome and nucleotide sequence of the gene coding for the two major polypeptides of the Hepatitis B surface antigen (HBs Ag)

Abstract: The structural gene coding for both polypeptides I and II which are the two major polypeptides of the Hepatitis B surface antigen, is found to be localized on the viral genome. This gene, referred to as gene S, is located in the partially single stranded region. It maps between positions 73.6 and 95.1% of the genome length. It is composed of 678 nucleotides, which correspond to a theoretical polypeptide of 25,422 molecular weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Nucleic acid homologies between the cloned HBV and WHV DNAs were detected by Southern gel hybridization (3). Cloning of the complete HBV DNA genome by using XgtWES-XB and subsequent studies using this clone have been reported (4)(5)(6)(7).…”
Section: Recently Summers Et Al (1) Demonstrated That the Human Hepamentioning
confidence: 99%
“…Nucleic acid homologies between the cloned HBV and WHV DNAs were detected by Southern gel hybridization (3). Cloning of the complete HBV DNA genome by using XgtWES-XB and subsequent studies using this clone have been reported (4)(5)(6)(7).…”
Section: Recently Summers Et Al (1) Demonstrated That the Human Hepamentioning
confidence: 99%
“…The antigenicity and immunogenicity of this protein (designated S-protein) depends on the maintenance of disulphide bonds (Vyas et al, 1972;Sukeno et al, 1972;Dreesman et al, 1973). The open reading frame on HBV DNA coding for S protein (Charnay et al, 1979;Peterson et al, 1977) has the capacity to code for a protein consisting of 389 to 400 amino acids (depending on the antigenic subtype of HBV). The DNA sequence corresponding to this reading flame and preceding the gene for S-protein (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, information on the genetic organization of the virus was obtained from the nucleotide sequence of the genome. Genes coding for surface and capsid antigens and perhaps for DNA polymerase are located on the long strand of the genome (4)(5)(6)(7). However, nothing is known concerning virus gene expression and its regulation.…”
mentioning
confidence: 99%